„Frische Brot, lecker Brot, taze Brot“ – Eigene Muster in der Adjektivverwendung auf einem mehrsprachigen Wochenmarkt - Schumann, Kathleen (Linguistik Online, 2022)
In this study, I am going to show that speakers at a multilingual urban street market in Berlin established own patterns for the use of attributive adjectives in German. Besides perfectly cano-nical patterns for adjectival inflection and linearization, the data contain instances where uninflected adjectives precede or follow the noun (normal Pide, ‘regular pita bread’; Weintrauben lecker, ‘grapes delicious’) or where adjectives are inflected with a reduction morpheme -e (türkische Mokka, ‘Turkish mocha’). I am showing that these patterns occur highly systematic. Concerning the question of what factors might have influenced the emergence of these patterns, I argue that speakers pick up typological and language-internal tendencies and apply these to new grammatical contexts. The linguistic diversity at the market as the site of these linguistic developments plays a central role for that.